Administrative efficiency of IPS providers of health entities accredited in quality in Colombia (2019)
This study evaluated the efficiencies of the IPS health providers accredited in quality in Colombia. The normative framework associated with the Mandatory Quality System, the quality accreditation standards for the IPS and the Data Envelopment analysis models, related to the purely technical or administrative efficiency were used as theoretical support. As an epistemological conception, we worked with the logical positivism paradigm, with which the scientific verification and the logical analysis for the development of all the research were sought. The research type had an evaluative approach. As a population, 27 accredited IPS health service providers were taken, which lent their financial statements to the superintendence of health in 2015 and 2016. The inductive and deductive method was used. The information generated by the health superintendence and the Ministry of Health were used as primary sources. The DEA BCC-O model focused on the optimization of outputs was used as an analysis technique. As a result of this research, a method to evaluate the efficiencies of high-quality accredited IPSs in Colombia was provided. Likewise, it could be demonstrated with empirical evidence that the implementation of high-quality standards in the IPSs studied has a significant impact on administrative efficiency. The research showed that the best IPS accredited in Colombia was the Pablo VI Hospital in Bosa. © 2019 International Business Information Management Association (IBIMA).